2019
DOI: 10.1016/j.matchar.2019.109878
|View full text |Cite
|
Sign up to set email alerts
|

On the microstructural-textural characterization and deformation analysis of a nano/ultrafine grained Fe-20Cr-8Mn-0.3N duplex alloy with superior mechanical properties

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 76 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…In this regard, the reported results of micromechanical properties of constitutive phases (γ or α) are diverse. Austenitic phase could have higher, lower or equal hardness/elastic modulus compared with ferritic phase, depending on different variables such as specific processing route under consideration [20,21], chemical compositions (N content) [22][23][24][25][26], and microstructural/crystallographic texture of the individual phases [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the reported results of micromechanical properties of constitutive phases (γ or α) are diverse. Austenitic phase could have higher, lower or equal hardness/elastic modulus compared with ferritic phase, depending on different variables such as specific processing route under consideration [20,21], chemical compositions (N content) [22][23][24][25][26], and microstructural/crystallographic texture of the individual phases [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, austenite or ferrite could not be defined by massive indentation technique, unless those phases were already determined by microstructural characterization techniques. On the other hand, in some cases, depending on alloying elements and processing conditions, austenite and ferrite show relatively similar mechanical properties (H and E) [21][22][23][24][25][26][27][28][29]; thus, assigning/correlating the obtained H or E to/with an austenite or ferrite phase would be complicated. Attempting to address satisfactorily this challenge for DSSs, a novel high-speed nanoindentation mapping technique in conjunction with microstructural characterization techniques were here employed.…”
Section: Introductionmentioning
confidence: 99%
“…After annealing and subsequent quenching, the ductility is restored with the formation of austenite and microstructure reallocation, while hardness, yield, and tensile strength are reduced [15,33,34]. More specifically, the reported findings concerning the mechanical properties of the constituent phases (ferrite and austenite) of conventionally manufactured DSS/SDSS at the nanoscale display considerable variation [40][41][42]. The hardness and elastic modulus of the austenitic phase can differ-being higher, lower, or on par with those of the ferritic phase.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, It has been found that the hardness of two phases of LDSS exhibits a large difference under high-temperature conditions, which is the reason why the alloys instabilize and crack during hot deformation [7,8]. As a result of lower alloying element content in LDSS, the stability of the austenitic phase is reduced, and strain-induced martensite transformation (SIMT) occurs when the material is deformed [9,10]. There are two types of martensite named quenched martensite and strain-induced martensite formed from the metastable austenite phase [11].…”
Section: Introductionmentioning
confidence: 99%